DIGITAL KIDS ON DISPLAY: UNVEILING CHILD INFLUENCING PRACTICES, PLATFORM PREFERENCES, SOCIETAL PERCEPTIONS, AND THREAT LANDSCAPE - Subhiksha R, Dr. Bhargavi D Hemmige (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In an era dominated by digital connectivity, the emergence of child influencers has become a prominent and intricate facet of online culture. This study, titled "Digital Kids on Display: Unveiling Child Influencing Practices, Platform Preferences, Societal Perceptions, and Threat Landscape," endeavors to unravel the complexities surrounding child influencers. The first objective seeks to comprehend the nuances of child influencing, exploring the strategies employed and the implications for the children involved. Moving on, the second objective conducts a meticulous analysis of the social media platforms that serve as the primary playgrounds for child influencers. Delving into the third objective, the study investigates societal opinions on child influencing, offering insights into public perceptions, ethical concerns, and societal attitudes. Finally, the fourth objective undertakes a comprehensive threat analysis to identify potential risks and vulnerabilities inherent in child influencing practices. By addressing these objectives, this research contributes to a deeper understanding of the evolving landscape of child influencers and the implications for digital parenting and child well-being.